Synthesis and characterization of value added catalysts zeolite beta using environmentally detrimental flyash - Kasture, M. W.; Bokade, Vijay V.; Joshi, P. N.; Kumar, R. (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
Fly ash is a major byproduct of Thermal power plant, which makes a lot of pollution to the environment due to its fineness. When a large amount of fly ash is dumped in the places near to power plants, it mixes in all segment of environment like water, air as well as soil. Though it can be utilized for different useful purposes, due to the lack of technical knowledge about how and proper motivation, no progress has been made in its utilization. It has been demonstrated that the fly ash can be used for making a value added catalyst zeolite beta by using simple and low cost process. In the present paper it is demonstrated that the fly ash can be used as a source of silica and alumina in the synthesis of value added catalyst zeolite beta. Moreover, the influence of different silica sources such as tetraethylortho silicate, silica sol and fumed silica on the physiochemical characteristics of well crystallized zeolite beta was also studied. The detailed characterization was carried out by using powder XRD, (27)Al and (29)Si MAS NMR, chemical analysis and low temperature nitrogen adsorption. Based on the data obtained from various systems containing different silica source, fumed silica is found to be most efficient source materials and showed superiority in the uniformity of aluminum distribution and possesses higher surface area.

Synthesis of Bio-diesel and Bio-lubricant by transesterification of vegetable oil with lower and higher alcohols over heteropolyacids supported by clay (K-10) - Bokade, Vijay V.; Yadav, G. D. (Process Safety and Environmental Protection, 2007)
{The use of different lower and higher alcohols viz; methanol, ethanol, n-propanol and n-octanol, for the synthesis of methyl, ethyl, propyl and octyl fatty acid esters by transesterification of vegetable oil (triglycerides) with respective alcohols also known as `Bio-diesel' and `Biolubricants' was studied in detail. The reactions were carried out in a batch process. The activity with different supports like clay (K-10), activated carbon, ZSM-5, H-beta and TS-1 were compared. The superacids (heteropolyacids, HPA) viz; Dodeca-Tungstophosphoric acid [
Keywords: coprecipitation; lithium aluminate; Microemulsion; Nanoparticles; sol-gel; Surfactants

Synthesis of pharmaceutical intermediates by toluene benzylation over heteropoly acids on different support - Bokade, Vijay V.; Yadav, G. D. (Journal of Natural Gas Chemistry, 2007)
{Selective formation of pharmaceutical intermediates like diphenylmethane, dimethyl-diphenylmethane, benzyl toluene and benzoic acid by liquid phase, toluene benzylation with benzyl chloride as a benzylating agent, was systematically studied over plane clay (K-10, montmorillonite), plane H-Beta, plane MFI structured titanosilicate (TS-1) and heteropoly acids [
Keywords: heteroassembly; nanoplates; polyfunctional capping agents; shape selective synthesis of gold-silver nanostructures; surface confinement

Selective N-alkylation of aniline with methanol over a heteropolyacid on montmorillonite K10 - Nehate, Manoj; Bokade, Vijay V. (Applied Clay Science, 2009)
N-methylaniline is an industrially important product in the manufacture of paper, textile dyes, drugs, perfumes and explosives. The vapour phase alkylation of aniline with methanol forming N-methylaniline is advantageous over liquid phase alkylation. In present study, vapour phase methylation of aniline over dodecatungestophosphoric acid supported on K10 montmorillonite was systematically studied and optimization of process parameters was carried out. The 20% m/m DTPA/K10 was found to be optimum with 79% aniline conversion and 99% N-methylaniline selectivity. The reaction required milder operating conditions than reported for commercial catalysts. We also studied the feasibility of 20% m/m DTPA/K10 as a catalyst for the alkylation of aniline with other alcohols like ethanol, n-propanol, iso-propanol and n-butanol. The activity of 20% m/m DTPA/K10 decreased with increasing carbon number. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alkylation; Aniline; Heteropolyacid; montmorillonite K10; N-methylaniline

Selective synthesis of cumene by isopropylation of benzene using catalytic membrane reactor - Bokade, Vijay V.; Kharul, Ulhas K. (Chemical Engineering Journal, 2009)
Selective isopropylation of benzene to cumene is demonstrated using catalytic membrane reactor (CMR), to our knowledge for the first time and the performance was evaluated against conventional plug flow reactor (PFR). Almost complete elimination of byproducts like polyalkylated benzene and higher aromatics could be made possible by using CMR. These are present in significant amount when reaction is carried out with PFR. The cumene selectivity increased up to a maximum of 97.25% by CMR as against 90.05% with conventional PFR. The effect of reaction parameters that can greatly influence the process economics, such as liquid hourly space velocity (LHSV), reactant mole ratio and catalyst/reactor volume ratio were investigated. Changes in these parameters made for CMR are industrially advantageous. The process by CMR is more economical and ecofriendly than PFR as far as milder process parameters (higher LHSV, lower reactant feed mole ratio, less catalyst require, etc.) and process intensification (reaction and separation in single reactor) are concerned. The study provides new insights for benzene isopropylation reaction. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Benzene; Catalytic membrane reactor; cumene; Diisopropyl benzene; Friedel-Craft alkylation

Synthesis of N-methylaniline by aniline alkylation with methanol over Sn-MFI molecular sieve - Niphadkar, P. S.; Joshi, P. N.; Gurav, H. R.; Deshpande, Suvarna S.; Bokade, Vijay V. (Catalysis Letters, 2009)
Sn-MFI molecular sieves (Tin silicalite-1) with SiO(2)/SnO(2) molar ratio of 50-150 were synthesized and characterized. Elemental analysis, XRD and DRUV-vis confirmed that prepared samples were of MFI zeolite structure and Sn was incorporated in MFI framework. Vapor phase methylation of aniline over Sn-MFI was systematically studied and optimizations of process parameters were carried out. Sn-MFI (SiO(2)/SnO(2) = 50) was found to be optimum catalyst with 55% aniline conversion and 60% N-methylaniline selectivity. At lower space velocity (higher contact time) of 1 h(-1), aniline conversion was found to be increased to 71% with reduction in N-methylaniline selectivity to 39% and increased in N,N-dimethylaniline selectivity to 58%. The reaction follows first order kinetics with respect to aniline having activation energy of 7.3 kcal/mol.
Keywords: Aniline; Lewis acid; Methanol; N-methylaniline; Sn-MFI

Synthesis of ethyl acetate by esterification of acetic acid with ethanol over a heteropolyacid on montmorillonite K10 - Gurav, Hanumant; Bokade, Vijay V. (Journal of Natural Gas Chemistry, 2010)
In present work, liquid phase esterification of acetic acid with ethanol over dodecatungestophosphoric acid (DTPA) supported on K10 mommorillonite was systematically studied and optimization of process parameters was carried out The 20% m/m urpAtK tO was found to be the optimum catalyst with 90% acetic acid conversion and 100% ethyl acetate selectivity The study was also explored to see the feasibility of 20% m/m DTPA/K10 as a catalyst for the alkylation of acetic acid with other alcohols like methanol, iso-propanol and sr-butanol. The 20% m/m DTPA/K10 has shown increased activity with the increase in carbon number, at the same alcohol reflux The results are novel
Keywords: Acetic acid; Ethanol; ethyl acetate; Heteropolyacid; montmorillonite K10

Selective synthesis of propofol (2,6-diisopropylphenol), an intravenous anesthetic drug, by isopropylation of phenol over H-beta and H-mordenite - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (RSC Advances, 2014)
Propofol (2,6-diisopropylphenol/DIPP) is the world's most widely used intravenous general anesthetic and is typically synthesized by isopropylation of phenol over an acid catalyst. It is highly difficult to stabilize bio-oil containing phenolic compounds. The isopropylation of this phenol (a model compound representing species in bio-oils) is one of the options to stabilize the bio-oil and convert it into valuable products. Probably for the first time, H-beta- and H-mordenite-catalysed vapour phase isopropylation of phenol with isopropyl alcohol (IPA) was studied to selectively synthesize DIPP. The optimization of various operating parameters such as molar ratio (phenol : IPA), weight hourly space velocity (WHSV), reaction temperature and time on stream were performed. H-beta (94% phenol conv. and 56% DIPP sel.) was found to be a potential and more active catalyst than H-mordenite (68% phenol conv. and 43% DIPP sel.) at optimized process parameters. A kinetic model is proposed to probe the intricate reaction kinetics and validated (R-2 > 0.98) by the experimental results. H-beta catalyst was observed to be stable for more than 25 h with 94% phenol conversion and 56% selectivity towards DIPP at optimized process parameters. The phenol conversion and DIPP selectivity obtained in the present study are higher than those reported so far. The activation energy obtained for isopropylation of phenol with IPA over H-beta is calculated to be 25.39 kJ mol(-1).

Synthesis of non-toxic triethyl citrate plasticizer by esterification of renewable citric acid using modified zeolite - Nandiwale, Kakasaheb Y.; Borikar, Sanjay P.; Bokade, Vijay V. (Clean-Soil Air Water, 2015)
Triethyl citrate (TEC), a non-toxic plasticizer, was synthesized by esterification of renewable citric acid (CA, from entire waste of oranges) with ethanol over modified H-ZSM-5 (HZ-5) zeolite. Different micro-meso composites (M-HZ-5) with varying crystallinities were prepared by alkaline treatment of HZ-5. M-HZ-5(0.6) (87% crystallinity) was observed to be a potential and environmentally benign catalyst with 96% CA conversion, 64% TEC selectivity (61.44% TEC yield), and a reusability of six cycles. The probable catalytic mechanism of esterification was also proposed.
Keywords: Biowaste; Catalysts; green chemistry; Micro-mesopre composites; reusability

Sustainable catalytic process for synthesis of triethyl citrate plasticizer over phosphonated USY zeolite - Nandiwaleand, Kakasaheb Y.; Bokade, Vijay V. (Bulletin of Chemical Reaction Engineering and Catalysis, 2016)
Fruits wastage is harmful to health and environment concerning spreading diseases and soil pollution, respectively. To avoid this issue, use of citrus fruit waste for the production of citric acid (CA) is one of viable mean to obtain value added chemicals. Moreover, synthesis of triethyl citrate (TEC), a non-toxic plasticizer by esterification of CA with ethanol over heterogeneous catalyst would be renewable and sustainable catalytic process. In this context, parent Ultrastable Y (USY) and different percentage phosphonated USY (P-USY) zeolites were used for the synthesis of TEC in a closed batch reactor, for the first time. The synthesized catalysts were characterized by N2-adsorption desorption isotherm, powder X-ray diffraction (XRD) and NH3 temperature programmed desorption (TPD. Effect of reaction conditions, such as the molar ratio of ethanol to CA (5:1 - 20:1), the catalyst to CA ratio (0.05-0.25) and reaction temperature (363-403 K), were studied in view to maximizing CA conversion and TEC yield. Phosphonated USY catalysts were found to be superior in activity (CA conversion and TEC yield) than parent USY, which is attributed to the increased in total acidity with phosphonation. Among the studied catalysts, the P2USY (2% phosphorous loaded on USY) was found to be an optimum catalyst with 99% CA conversion and 82% TEC yield, which is higher than the reported values. This study opens new avenues of research demonstrating principles of green chemistry such as easy separable and reusable catalyst, non-toxic product, bio-renewable synthetic route, milder operating parameters and waste minimization.

Synthesis of ethyl furfuryl ether (potential biofuel) by etherification of furfuryl alcohol with ethanol over heterogenized reusable H1Cs2PW12O40 catalyst - Mulik, Nagesh L.; Niphadkar, Prashant S.; Bokade, Vijay V. (Research on Chemical Intermediates, 2020)
{Ethyl furfuryl ether (EFE) considered as potential biofuel can replace petroleum diesel up to 100%. EFE also has efficient blending properties with biodiesel to improve its cold flow properties. Herein we demonstrate efficient synthesis of EFE by etherification of renewable furfuryl alcohol (FAlc) with ethanol over heterogenized heteropoly acids. Cs-exchanged heterogenized heteropoly acid (H3-xCsxPW12O40
Keywords: B; etherification; Ethyl furfuryl ether; Furfuryl alcohol; H3-xCsxPW12O40; Heterogenized heteropoly acid; L ration